ANALISA PERGULATAN HUKUM DAN FENOMENA LINGKARAN KEHIDUPAN NELAYAN DI SECANGGANG LANGKAT - Tarigan, Fernando; Aspan, Henry; Simanjuntak, Hotmaida; Zarzani, T Riza; Anwar, Yohny (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
Fisherman's life is generally synonymous with poverty, this can be seen from the slum state of residence and the houses of a waterless stage and poor health environment and the low education of the fishermen. The problems of this research are. a. How is the life of fishermen in Secanggang village Langkat, b. how the government's role in tackling the life of fishermen in a cleavage c. What should the government do for the future of fishermen in Secanggang village langkat.This research is a juridical descriptive whose data source is done by field research and documentation, data collecting is done by interview, quieter, observation, research result, fisherman at Secanggang village Langkat still using traditional fishing gear and 35% fishermen do not have fishing facilities especially bots, fishermen live depending on weather and natural conditions, and sea waves, to sustain family life the fishermen have to borrow money at collector which will be paid later with the catch of the fish. The children in Secanggang village Langkat do not criticize education because they prefer to catch fish and get money and the children just finish junior high school to continue to high school is very difficult because of unfavorable economic conditions and transportation costs are quite high.